Sucrose and nitrogen supplies regulate growth of maize kernels - Cazetta, J. O.; Seebauer, JR; Below, F. E. (Academic Press Ltd, 1999)
The growth of maize (Zea mays L.) kernels depends on the availability of carbon (C) and nitrogen (N) assimilates supplied by the mother plant and the capacity of the kernel to use them. Our objectives were to study the effects of N and sucrose supply levels on growth and metabolism of maize kernels. Kernel explants of Pioneer 34RO6 were cultured in vitro with varying combinations of N (5 to 30 mM) and sucrose (117 to 467 mM). Maximum kernel growth was obtained with 10 mM N and 292 mM sucrose in the medium, and a deficiency of one assimilate could not be overcome by a sufficiency of the other. Increasing the N supply led to increases in the kernel sink capacity (number of cells and starch granules in the endosperm), activity of certain enzymes (soluble and bound invertases, sucrose synthase, and aspartate aminotransaminase), starch, and the levels of N compounds (total-N, soluble protein, and free amino acids), and decreased the levels of C metabolites (sucrose and reducing sugars). Conversely, increasing the sucrose supply increased the level of endosperm C metabolites, free amino acids, and ADPG-PPase and alanine transaminase activities, but decreased the activity of soluble invertase and concentrations of soluble protein and total-N. Thus, while C and N are interdependent and essential for accumulation of maximum kernel weight, they appear to regulate growth by different means. Nitrogen supply aids the establishment of kernel sink capacity, and promotes activity of enzymes relating to sucrose and nitrogen uptake, while sucrose regulates the activities df invertase and ADPG-PPase. (C) 1999 Annals of Botany Company.
Keywords: Zea mays; maize; In vitro; Invertase; ADPG-PPase; media composition; sucrose; Nitrogênio; C/N